Species of Bittacomorphella Alexander from China with descriptions of two new species (Diptera: Ptychopteridae) - Kang, Zehui; Wang, Junchao; Yang, Ding (Zootaxa, 2012)
The genus Bittacomorphella (Alexander) is newly recorded from the Chinese mainland. Two species, Bittacomorphella gongshana sp. nov. and B. zhaotongensis sp. nov., are described. A key to males of described Bittacomorphella from the Oriental region is presented.